Ultrasound-assisted synthesis of substituted 2-aminobenzimidazoles, 2-aminobenzoxazoles, and related heterocycles - Phakhodee W. (2017)
© 2016 Elsevier Ltd A sonochemical method for the synthesis of 2-aminobenzimidazoles and 2-aminobenzoxazoles, as well as chiral aminooxazolines and a chiral substituted quinazolin-5-one is reported. Using the Ph 3 P–I 2 system in the presence of triethylamine as a desulfurization agent, monothioureas prepared in situ from the reaction of bis-nucleophiles with isothiocyanates underwent rapid cyclization to afford a variety of N-heterocyclic compounds in good to excellent yields under mild conditions.